Attitudes toward opioid substitution therapy and pre-incarceration HIV transmission behaviors among HIV-infected prisoners in Malaysia: implications for secondary prevention. - Bachireddy, Chethan; Bazazi, Alexander R; Kavasery, Ravi; Govindasamy, Sumathi; Kamarulzaman, Adeeba; Altice, Frederick L (Drug and alcohol dependence, 2011)
Pre-incarceration HIV transmission behaviors and current attitudes toward opioid substitution therapy (OST) among HIV-infected male prisoners in Malaysia have important implications for secondary HIV prevention efforts.
Keywords: Adult; Attitude; Comorbidity; Health Knowledge, Attitudes, Practice; HIV Infections; Humans; Malaysia; Male; Middle Aged; Needle Sharing; Opiate Substitution Treatment; Opioid-Related Disorders; Prisoners; Prisons; Risk-Taking; Secondary Prevention; Sexual Behavior; Substance Abuse, Intravenous; Time Factors; Unsafe Sex; Young Adult